Modeling of separated flow in the inlet of a circular suction channel - Averkova, O.A.; Logachev, I.N.; Logachev, K.I..; Puzanok, A.I.; Khodakov, I.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2013)
Methods for the mathematical modeling of separated flows in the inlet of a suction channel are discussed on the basis of the discrete vortex peculiarities of circular and polygonal shapes. The problems in stationary, nonstationary, axisymmetric, and quasiaxisymmetric formulations are considered. The calculated velocity values are compared with experimental data obtained by other authors. The conclusion on the possibility of using vortex polygonal elements to study the flows in the action spectra of influx and extract devices in three dimensions is made. The work was supported by the Russian Federation President Fellowship Council (project RS–588.2012.8), the Russian Foundation for Basic Research (project 12–08–97500–r_center_а), and the strategic plan of Belgorod State Technological University (project А–10/12).